Research method for geological-geotechnical analysis of unstability of slopes by landslide zona Ronquillo-Corisorgona Cajamarca-Perú - Rodríguez Cruzado, Reinaldo (2017)
The research analyzes the geostructural, geomorphological and geomechanical behavior of rock masses of Farrat, Inca, Chulec and Pariatambo Formations, found in Ronquillo-Corisorgona area massifs have unstable slopes by strong fracturing caused by the regional tectonics and local as well as superficial and deep weathering conditions that have determined geodynamic events as a paleodeslizamiento approximately 500 meters long and slopes between 19° and 45°, intermediate landslides, disturbed areas and a recent slide; evidence to determine the likelihood of a future large sliding in the Cerro Ronquillo. Consequently aimed to analyze the slope instability associated with internal factors, and their intrinsic characteristics conditioned by the material properties and resistance, and extrinsic, related to the morphology of the slopes and environmental conditions; and external or triggers such as water infiltration and seismicity. By correlating these variables by Geostructural analysis of information from each control point using Software Dips and incidence of hydrological variable parameters precipitation and infiltration, we obtained safety factors in three geological sections using geomechanical parameters, water table and seismicity, according Bieniawski89 and Software RocData, having minimum and maximum FS 0.524 1,609. Tested the hypothesis by correlation and causality conditions geological, geomechanical and numerical models, which the Geological and Geotechnical Operational and Conceptual Model of Instability Hillsides essence of the investigation had raised initially defined.